Synthesis of Indicator Strains and Density of Ribonucleic Acid-Containing Coliphages in Sewage - Dhillon, Elvera K. S. (1974)
Escherichia coli strains freshly isolated from natural sources are inefficient indicators of coliphages present in sewage. Four E. coli strains recently isolated from clinical specimens were mutagenized to obtain lac(-) mutants. Such mutants were infected with an F′lac(+) sex factor of E. coli K-12. Pairs of isogenic lac(-) and lac(-)/F′lac(+) strains were used as indicators of coliphages present in sewage, and it was found that such strains can be effectively used for a direct and almost selective enumeration of F-specific coliphage contents of sewage samples. Serological tests were applied to a number of F-specific phages isolated. All the isolates that were tested fell into two distinguishable antigenic classes: members of one class being related to ribonucleic acid (RNA) phage MS2 and those of the other being related to another RNA phage, namely, Qβ. MS2-related phages have been found to be more widely distributed than the Qβ related phages. Most habitats sampled were found to yield only one or the other kind of phage. Single-stranded deoxyribonucleic acid-containing F-specific phages were not detectable by the methods employed by us.